Association of MicroRNAs With Risk of Stroke: A Meta-Analysis - Deng, Yidong; Huang, Peijian; Zhang, Fan; Chen, Tao (Frontiers in Neurology, 2022)
Objectives Altered expression of microRNAs (miRNAs) may contribute to disease vulnerability. Studies have reported the involvement of miRNA in the pathophysiology of ischemic stroke. Methods We performed a meta-analysis of data from 6 studies that used a panel of miRNAs with altered expressions to diagnose ischemic stroke with the Bayesian framework. The I2 test and Cochran's Q-statistic were used to assess heterogeneity. Funnel plots were generated and publication bias was assessed using Begg and Egger tests. Results On summary receiver operating characteristics (SROC) curve analysis, the pooled sensitivity and specificity of altered miRNA expressions for diagnosis of ischemic stroke was 0.92 (95% confidence interval [CI] 0.80–0.97) and 0.83 (95% CI 0.71–0.90), respectively; the diagnostic odds ratio was 54.35 (95% CI 20.39–144.92), and the area under the SROC curve was 0.93 (95% CI 0.90–0.95). Conclusions Our results showed a link between dysregulation of miRNAs and the occurrence of ischemic stroke. Abnormal miRNA expression may be a potential biomarker for ischemic stroke.